Body image, quality of life and perceived control in patiens with colorectal cancer: a review - Senabre, Pedro (2021)
In the present article we aimed to realize a systematic review of the literature about the relationship between three subjects (body image, Quality of life and perceived control) and patients with colorectal cancer. The diagnosis of a chronic disease is always a source of stress that can lead to loss of control, anxiety, a feeling of incapacity and that requires adaptation on the part of the patient. We used several databases: EBSCO, PubMed, Medline, Google Academic and books specialized in these subjects. We conclude that there is a strong relation between body image, quality of life and colorectal cancer; further research is needed about the connection between perceived control and colorectal cancer.